Importancia de los elementos climáticos en la variación florística temporal de pastizales semidesérticos - Aguado Santacruz, Gerardo Armando; Garcia Moya, Edmundo; Velasco Gonzalez, Cruz; Flores Flores, Jose Luis (Instituto de Ecología, A.C., 1996)
Using a multivariate direct ordination approach, Partial Canonical Correspondence Analysis, we investigated in semidesert grasslands of northeastern Jalisco the relationship of annual variation in community compositional patterns to weather dynamics, once the soil, management and time influences fitted. Temporal floristic variation patterns were mainly influenced by summer precipitation and summer maximum temperature (P=0.01). Weather exerted a greater influence on floristic variation than soil. Annual species were abundant during rainy years, while perennial grasses optima were located at intermediate levels relative to the evaluated climatic factors.